Marketing crafts and visual arts : the role of intellectual property : a practical guide (ITC/WTO GenevaCH, 2003)
Provides a basic knowledge and understanding of marketing techniques and of intellectual property to artisans, craft entrepreneurs and visual artists, to enhance the chances of their business success.
Bibliography: p. 134-135